Bakteriologis Makanan Jajanan Pada Warung Sari Laut Di Kecamatan Somba Opu Kabupaten Gowa - Muhammad Fais Satrianegara; Husnul Hatimah (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
One source oftransmission of the disease and the causes of food poisoning is food and drinks that do not meet hygiene requirements. Hygiene of foods and beverages among others influenced by the hygiene of cookware and cutlery that used in the food supply process. The purpose of this study was to determine the description of bacteriological quality on the Sari Laut stalls in Somba Opu District, Gowa Regency. This research is quantitative with Descriptive observational approach. The population consists of all Sari Laut Stalls in Somba Opu District, Gowa Regency. The sample consists of two stalls select edusing purposive sampling technique, with sampling technique by purchase. The results showed that both of two stalls were studied contained 14 samples of food. Food samples qualified ISO 73882009 about Limit of Microbial Contaminationin Food as many as 12 samples, which are cucumber samples A and B, bean A and B, cabbage A and B, rice A and B, basil A and B, and chickenfried A and B. Samples that did not qualify, there are two, namely chili sauce A and B. Expected to conduct examinations and continuous guidance to the  merchant to feel responsible for the quality of food served to avoid the diseaseas a result of street food and improve personal hygiene and environmental sanitation around the location of the business. Keywords  : Total Microbe, Street Food, ISO 7388.2009